If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 13 = -67 + -10x Reorder the terms: 13 + 6x = -67 + -10x Solving 13 + 6x = -67 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 13 + 6x + 10x = -67 + -10x + 10x Combine like terms: 6x + 10x = 16x 13 + 16x = -67 + -10x + 10x Combine like terms: -10x + 10x = 0 13 + 16x = -67 + 0 13 + 16x = -67 Add '-13' to each side of the equation. 13 + -13 + 16x = -67 + -13 Combine like terms: 13 + -13 = 0 0 + 16x = -67 + -13 16x = -67 + -13 Combine like terms: -67 + -13 = -80 16x = -80 Divide each side by '16'. x = -5 Simplifying x = -5
| 3x^4-21=0 | | 6x+5x+4+8=7x+4+3x | | 102-4x=4x+6 | | -6y+3=-7y+6 | | 18-n=10 | | 2-4x=17-7x | | 4p+7=13+3p | | 7+7+7+7+7+7+7+7-7-7-7-7-7-7-7-7-x+x= | | 7+7+7+7+7+7+7+7-7-7-7-7-7-7-7-7= | | 9+12x=42+x | | 2x^3+6x^2+18x+54=0 | | x^4+2x^3+3x^2+18x+54=0 | | 2x+2y=44 | | 2.6y+2=0.6y-6 | | 30-2r=7 | | 13-8x=101-36x | | 4x+12=-12-8x | | 120=(3x+2)x | | 98-4x=2x+14 | | -18-4x=9-7x | | 5x^2-8x=12 | | 10+7x=70+x | | 4-2y=-18 | | 52x-99=-4x+16 | | (2x+3)(x+2)=120 | | 6x+x+7=4 | | (2x+3)(x+2)=60 | | 52-6x=12x+22 | | 6-10x=94-38x | | 6x+8=-72-10x | | 7(x+2)=5x+1 | | 4x+8=50-2x |